Determining the cost of design work using aggregated indicators of the estimated cost of housing reconstruction - Gritsenko О.; Kovalyova, L.; Zapiechna, Y. (Ways to Improve Construction Efficiency, 2022)
This article is devoted to determining the estimated cost of project work with the help of aggregated indicators of housing reconstruction, identification of priority areas and the ability to economically justify the reconstruction of damaged housing stock of Ukraine. Estimates of Ukraine state that the determination of the estimated cost of designing the construction of industrial and non-industrial facilities is the application of average percentages of the cost of design work to the calculation base. The use of the method of analogous object is not reliable because the qualification of the author of estimates is limited, as a rule, by a small number of projects of such analogous objects in a particular project enterprise. The authors propose to determine the value of similar objects using the appropriate methodology, using it also to restore the damaged housing stock at the following stages of design: sketch design, feasibility study, project. The method determines the limits of fluctuations of specific values of technical and economic indicators for homogeneous groups of housing reconstruction objects and regression equations which determine the standards of investor estimated value of objects. To verify these statements, an example of determining the estimated value of the specific values of the consolidated estimate (12 chapters, estimated profit, administrative costs, risks, inflation, taxes and refunds) depending on the specific values of technical and economic indicators of the new object based on homogeneous regression equations On the basis of the given equations on homogeneous groups the search of objects with sizes of specific technical and economic indicators similar to sizes of similar indicators of researched object is conducted. The appropriate method allows you to quantify the estimated value of the damaged housing stock and determine the effectiveness of the investment used.